Functional outcome and CEUS-assessed deltoid muscle vitality after fracture-specific versus standard prosthetic design in reverse shoulder arthroplasty for trauma - Doll, Julian; Neide, Arndt; Mick, Paul; Brunnemer, Ulf; Schmidmaier, Gerhard; Fischer, Christian (Journal of orthopaedic research, 2022)
Functional outcome after reverse-shoulder-arthroplasty (RSA) in proximal humerus fractures (PHF) depends on deltoid muscle integrity and successful reattachment of the tuberosities for best possible recovery of rotator-cuff function. In this monocentric, prospective, randomized, controlled trial we investigated whether a reverse-fracture-prosthesis (RFP) with a metaphyseal fenestrated stem achieved superior shoulder and muscle function compared to a common reverse-prosthesis (RP) design for patients with PHF. Our hypothesis was that patients with RFP may achieve a superior healing rate of the greater tuberosity (GT) compared to patients receiving RP, which translates to significantly higher clinical outcome and functional scores as well as differences in deltoid muscle microperfusion. Forty-four patients with PHF were randomized preoperatively to one of the prosthesis types in RSA between 2018 and 2020 (22 with RFP and 22 with RP) and prospectively assessed 6 months after surgery. We assessed osteointegration of the GT with radiographs 1 day and 6 months postoperatively and examined shoulder function and patient satisfaction by using established shoulder scores. A contrast-enhanced ultrasound (CEUS) examination of both shoulders was performed to quantify intramuscular blood flow and evaluate vitality of the deltoid muscle. None of the functional and psychosocial scores or radiographs and ultrasound examinations showed significant differences between the RSA designs. The constant-Murley score (p = 0.384) and active anterior-elevation-abduction, and external rotation were comparable between the RFP and RP group. Similar healing rates of the GT were observed (p = 0.655). CEUS-assessed deltoid microperfusion revealed equivalent muscle vitality for both groups (p = 0.312). Level of evidence: Level II; Randomized Controlled Trial; Treatment Study. Clinical significance: The radiographic evaluation for the investigation of the GT healing rate indicates that the proclaimed benefits of the fracture prosthesis with fenestration design might not be as great as expected.